Urine dipstick analysis for identification of runners susceptible to acute kidney injury following an ultramarathon - Hoffman, M. D.; Stuempfle, K. J.; Fogard, K.; Hew-Butler, T.; Winger, J.; Weiss, R. H. (Journal of Sports Sciences, 2013)
This study examined whether urine dipstick testing might be useful to predict the development of acute kidney injury after an ultramarathon. Participants in the 2011 161-km Western States Endurance Run underwent post-race blood and urine dipstick analyses. Of the 310 race finishers, post-race urine dipstick testing was completed on 152 (49%) and post-race blood also was obtained from 150 of those runners. Based on "injury" and "risk" criteria for acute kidney injury of blood creatinine 2.0 and 1.5 times estimated baseline, respectively, 4% met the criteria for injury and an additional 29-30% met the criteria for risk of injury. Those meeting the injury criteria had higher creatine kinase concentrations (P < 0.001) than those not meeting the criteria. Urine dipstick tests that read positive for at least 1+ protein, 3+ blood, and specific gravity = 1.025 predicted those meeting the injury criteria with sensitivity of 1.00 (95% confidence interval [CI] 0.54-1.00), specificity of 0.76 (95% CI 0.69-0.83), positive predictive value of 0.15 (95% CI 0.06-0.30), negative predictive value of 1.00 (95% CI 0.97-1.00), and likelihood ratio for a positive test of 4.2. We conclude that urine dipstick testing was successfully able to identify those individuals meeting injury criteria for acute kidney injury with excellent sensitivity and specificity.